Agricultural eco-efficiency loss under technology heterogeneity given regional differences in China. (20th March 2020) - Han, Haibin; Ding, Tao; Nie, Lei; Hao, Zhenzhen
Abstract: What influences Chinese agricultural eco-efficiency (AEE)? Taking the underlying technology heterogeneity into account, we proposed an analytical framework which combines meta-frontier analysis and a non-separable hybrid model with undesirable output (Meta-Hybrid-U). The general aim of this study is to apply the proposed framework to measure the AEE in 30 provinces in China from 1997 to 2015 under the group-frontier and meta-frontier. The dimensions of management and technology were used for the deconstruction of the agricultural eco-inefficiency (AEI) of various provinces. The Dagum Gini coefficient method was used for decomposition of regional differences in the AEE in China. Three main results were found. First, the mean AEE of all Chinese provinces under the meta-frontier is low, and there is much room for improvement. Secondly, at the national level, the AEI is caused by both the management inefficiency (MI) and technology gap inefficiency (TGI). At the regional level, the AEI in eastern China is wholly caused by the MI, while the AEI in the central and western regions is caused by both the MI and TGI. Finally, during the studied period, there is an increasing trend for the overall Gini coefficient of the AEE in China. The regional differences in the AEE in China are mainly due to the inter-regional differences and the intensity of transvariation. The paper also includes some suggestions for policies to improve China's AEE and to reduce the inter-regional differences in China's AEE. Highlights: We employed Meta-Hybrid-U model to measure China's AEE. We examined the source of China's AEE loss from the dimensions of management and technology. The Dagum Gini coefficient was used for measurement and decomposition of regional differences in China's AEE. The AEE under the meta-frontier was not greater than the AEE under the group-frontier. There was an overall increasing trend for the overall Gini coefficient of the AEE in China.